The Phenomenon of Misconception about Bid’ah (Innovation) in Contemporary Muslim Society - Kamal-deen Olawale Sulaiman (Ar-Raniry: International Journal of Islamic Studies, 2022)
The controversial topic of innovation in Islam is one of the more important topics to explore. The correct understanding on bid’ah should remove much ambiguity and encountered tensions among contemporary Muslims society and ease the way for Muslims into progress. This paper therefore, intends to examine the concept of Bid’ah, highlights it is types and discuss the concept of bid’ah from the Qur’an the Sunna. Contextual analysis method will be used. Therefore, the exploration of legacies through Arabic literatures will be and analyze several academic writings from some relevant journals and paper works. The paper reveals that, there are evidences that new practices are not rejected, but are accepted and even rewarded. However, the practice concerned should be compatible with the dictates of the Shari’ah, otherwise it will be rejected. The opinion of those who condemn any new act without qualification comes from a misunderstanding of the sources of the Qur’an and Hadith. It clarified that, the introduction of new things into the religion ensures that Islam can apply itself to any given time and situation, and some new things have even been essential for its preservation and propagation. Thus “an innovation would become a bad bid’ah only, when it is in contradiction to any specific commandment of the Qur’an or specific hadith of the prophet, in all other cases, the bid’ah is termed as a good Bid’ah. It recommends that, the worldly innovations such as science and technology are not matters to be shunned or avoided.